2020
DOI: 10.1177/2045894020922118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical forces alter endothelin‐1 signaling: comparative ovine models of congenital heart disease

Abstract: The risk and progression of pulmonary vascular disease in patients with congenital heart disease is dependent on the hemodynamics associated with different lesions. However, the underlying mechanisms are not understood. Endothelin-1 is a potent vasoconstrictor that plays a key role in the pathology of pulmonary vascular disease. We utilized two ovine models of congenital heart disease: (1) fetal aortopulmonary graft placement (shunt), resulting in increased flow and pressure; and (2) fetal ligation of the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The ovine model of CHD with increased PBF and pressure used in this study replicates the typical features of the human disease, including elevated postnatal pulmonary arterial pressure and blood flow, with the associated derangements of pulmonary vascular structure and function (Reddy et al, 1995;Datar et al, 2012;Datar et al, 2014;Morris et al, 2018;Johnson Kameny et al, 2019;Zhu et al, 2020;Boehme et al, 2021). Although pulmonary Frontiers in Physiology frontiersin.org artery pressure and pulmonary to systemic blood flow ratio (Q_ p /Q_ s ) were not measured during these experiments, hemodynamics were measured in 5 shunt lambs during subsequent evaluations at between 8 and 15 weeks of age while under similar anesthetic conditions, which confirmed that these shunt lambs did experience increased PBF and elevated pulmonary artery pressure (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The ovine model of CHD with increased PBF and pressure used in this study replicates the typical features of the human disease, including elevated postnatal pulmonary arterial pressure and blood flow, with the associated derangements of pulmonary vascular structure and function (Reddy et al, 1995;Datar et al, 2012;Datar et al, 2014;Morris et al, 2018;Johnson Kameny et al, 2019;Zhu et al, 2020;Boehme et al, 2021). Although pulmonary Frontiers in Physiology frontiersin.org artery pressure and pulmonary to systemic blood flow ratio (Q_ p /Q_ s ) were not measured during these experiments, hemodynamics were measured in 5 shunt lambs during subsequent evaluations at between 8 and 15 weeks of age while under similar anesthetic conditions, which confirmed that these shunt lambs did experience increased PBF and elevated pulmonary artery pressure (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 70%
“…We have previously developed a surgical large animal model of increased PBF and pressure that we have used to study derangements of the pulmonary vasculature in this setting (Reddy et al, 1995;Black et al, 2000;Steinhorn et al, 2001;Black et al, 2003;Lakshminrusimha et al, 2007;Datar et al, 2012;Oishi et al, 2013;Datar et al, 2014;Johnson Kameny et al, 2019;Zhu et al, 2020;Boehme et al, 2021). In late gestation fetal lambs, a large 8 mm vascular graft is placed between the ascending aortic trunk and the main pulmonary artery (Reddy et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, the endothelium, smooth muscle cells, fibroblasts, inflammatory cells, circulating progenitor endothelial cells, and platelets all contribute to vascular remodeling. 9–11 Awareness of the role of genetic factors in PAH–congenital heart disease is increasing, with a number of genes being reported, including BMPR2 , SOX17 , TBX4 , and other rare inherited variants of NOTCH1 , PTPN1 , and RAF1 , as well as other genes with de novo variants. 12,13 PAH–congenital heart disease (group 1.4.4) occurs in left-to-right shunt lesions with 4 described clinical and hemodynamic profiles:…”
Section: Classification Of Ph Associated With Congenital Heart Diseasementioning
confidence: 99%